Longitudinal associations of polypharmacy and frailty with major cardiovascular events and mortality among more than half a million middle-aged participants of the UK Biobank - Chen, Li-Ju; Sha, Sha; Brenner, Hermann; Schöttker, Ben (Maturitas, 2024)
Background - Studies of the associations of polypharmacy and frailty with adverse health outcomes in middle-aged adults are limited. Furthermore, a potentially stronger association of polypharmacy with adverse health outcomes in frail than in non-frail adults is of interest. - Objective - To evaluate associations of frailty (assessed using a frailty index) and polypharmacy (defined as taking five or more drugs) with major cardiovascular events, cancer incidence, all-cause, cardiovascular disease-specific, and cancer-specific mortality. - Methods - Cox proportional hazards regression models were used to analyze 501,548 participants of the UK Biobank cohort study aged 40-69 years who were followed up for an average of 12 years. - Results - The prevalence of pre-frailty and frailty were 43.2 % and 2.3 %, respectively, and that of polypharmacy was 18.3 %. Although strongly associated with each other, frailty and polypharmacy were independently, statistically significantly associated with major cardiovascular events, cardiovascular disease-specific, and all-cause mortality. In addition, the hazard ratios of polypharmacy were stronger among (pre-)frail than non-frail study participants. No profound associations with cancer incidence and cancer mortality were observed. No sex and age differences were observed. - Conclusions - This large cohort study showed that polypharmacy and frailty are independent risk factors for major cardiovascular events, cardiovascular disease-specific and all-cause mortality in both middle-aged (40-64 years) and older people (≥ 65 years). In addition, the hazard ratios of polypharmacy were stronger among (pre-)frail than non-frail study participants. This underlines the need to avoid polypharmacy as far as possible not only in older but also in middle-aged subjects (40-64 years), especially if they are pre-frail or frail.